Research on Construction Safety Risk Assessment of New Subway Station Close-Attached Undercrossing the Existing Operating Station. (18th July 2019) - Luo, Zhenhua; Zeng, Li; Pan, Haize; Hu, Qijun; Liang, Bo; Han, Jianqiang
Abstract : With the large-scale construction of urban rail transit, it will lead to the intersection and transfer of various lines, resulting in more transfer stations. The transfer station is a collection point for multiple subway lines, which is difficult to construct and has a high construction risk. The construction of the new subway station and the operation of the existing subway station are mutually influenced during the close-attached undercrossing construction. Considering the two objectives of ensuring the smooth operation of the existing subway station and the safe construction of the new subway station, this paper comprehensively analyzes the possible safety risk factors during the construction of the new subway station close-attached undercrossing the existing operating station and identifies 75 preliminary risk factors by means of literature review and on-site investigation. Then the Delphi Method and Entropy Weight Method are used to screen the preliminary risk factors, and the main risk factors with greater influence are retained, so that 49 key risk factors are obtained. According to the list of key risk factors, a safety risk assessment index system including 2 first-level indexes, 12 second-level indexes, and 49 third-level indexes is established. Based on the index system, this paper establishes a safety risk assessment model by using Analytic Hierarchy Process (AHP) and Fuzzy Matter Element Method (FMEM). The model first calculates the weight of each index by using AHP, calculates the comprehensive correlation degree of each index by using FMEM, classifies the risk grade of each index according to the comprehensive correlation degree, and determines the risk grade of the project. Finally, the safety risk assessment model is applied to the Dongdalu Station project of Chengdu Rail Transit Line 8. The result shows that the risk grade of this project is moderate risk, which is basically consistent with the actual situation, indicating that the model has good practicability. In this paper, a new safety risk assessment model for subway close-attached undercrossing construction is proposed, which fills the gap in the field of safety risk assessment for the construction of the new subway station close-attached undercrossing the existing operating station.